A comparison of eating disorder psychopathology, appearance satisfaction, and self-esteem in overweight and obese women with and without binge eating. (April 2015) - Herbozo, Sylvia; Schaefer, Lauren M.; Thompson, J. Kevin
Abstract: This study investigated the differences in eating disorder psychopathology, appearance satisfaction, and self-esteem between 194 overweight/obese college women with and without binge eating. Participants were categorized as binge eating (BE; n  = 56) or non-binge eating (NBE; n  = 138) based on reports of binge eating at least once per week on average for the past 28 days and no episodes of vomiting or laxative use in the past 28 days. The BE group had significantly greater levels of eating, weight, and shape concerns and lower levels of appearance satisfaction and self-esteem than the NBE group. For the BE group, binge eating frequency was negatively correlated with dietary restraint. Results are generally consistent with studies utilizing clinical and community samples. The findings extend such research by examining binge eating in a sample of overweight and obese college women and indicating that overall appearance satisfaction is lower among women with binge eating. Study findings also highlight potential issues to address in obesity and binge eating intervention efforts for college populations. Future research is needed to replicate these findings in additional samples of college women and men. Highlights: We examined overweight/obese college women with and without binge eating. The binge eating group had greater eating disorder psychopathology. The binge eating group had lower appearance satisfaction and self-esteem. Binge eating frequency was negatively associated with dietary restraint.